2009
DOI: 10.1577/c08-008.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Striped Bass Larvae Transported from the Hudson River on Juvenile Abundance in Western Long Island Sound

Abstract: Freshwater flow can have a profound influence on the transport of larvae within large tidal estuaries, and tidal flow can transport larvae away from those estuaries. Our objectives were to (1) confirm that a combination of freshwater and tidal flows transported post‐yolk‐sac larvae (PYSL) striped bass Morone saxatilis from the Hudson River, New York, to western Long Island Sound (WLIS), a nearby nursery area, and (2) assess the effect of PYSL transported from the river on the abundance of juvenile striped bass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Successful recruitment of young‐of‐the‐year (age‐0) fishes has been linked to environmental processes (e.g., Boehlert and Mundy 1988; Hare and Govoni 2005; Lehodey et al 2006; Cury et al 2008). Previous studies have shown that nekton size (Hale and Targett 2018), temperature (Witting et al 1999; Lankford and Targett 2001; Hare and Able 2007; Carassou et al 2011; Yasumiishi et al 2016), salinity (Lankford and Targett 1994; Able et al 2009), freshwater input (Reist et al 2006; Carassou et al 2011), flow (Dunning et al 2009), and wind speed and direction (Nye et al 2014; Schieler et al 2014) can significantly affect transport, growth, and survival of multiple life stages of marine nekton. The NAO and AMO have been linked to trends in fisheries production, distribution, and abundance (Lehodey et al 2006).…”
mentioning
confidence: 99%
“…Successful recruitment of young‐of‐the‐year (age‐0) fishes has been linked to environmental processes (e.g., Boehlert and Mundy 1988; Hare and Govoni 2005; Lehodey et al 2006; Cury et al 2008). Previous studies have shown that nekton size (Hale and Targett 2018), temperature (Witting et al 1999; Lankford and Targett 2001; Hare and Able 2007; Carassou et al 2011; Yasumiishi et al 2016), salinity (Lankford and Targett 1994; Able et al 2009), freshwater input (Reist et al 2006; Carassou et al 2011), flow (Dunning et al 2009), and wind speed and direction (Nye et al 2014; Schieler et al 2014) can significantly affect transport, growth, and survival of multiple life stages of marine nekton. The NAO and AMO have been linked to trends in fisheries production, distribution, and abundance (Lehodey et al 2006).…”
mentioning
confidence: 99%